(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background: Knee osteoarthritis (KOA) is a common degenerative joint disorder, particularly in older adults, often worsened by obesity, malalignment, and inactivity. Conservative management through muscle strengthening and biomechanical correction helps delay disability. Objectives: This study investigated whether adding foot and ankle exercises improves symptoms in KOA patients beyond conventional proximal muscle training. Methods: Eighty participants were randomized into two groups. Group A received exercises for foot intrinsic and plantar flexors along with quadriceps, hamstrings, and hip abductors. Group B performed only proximal muscle exercises. KOOS scores were recorded at baseline and after six weeks. Results: Both groups improved significantly (p < 0.05), but Group A showed greater gains across all KOOS subscales (p < 0.05). Conclusion: Adding foot and ankle exercises enhances the effectiveness of KOA rehabilitation, supporting a kinetic-chain-based approach.